Nano Metal‐Organic Framework‐Derived Inorganic Hybrid Nanomaterials: Synthetic Strategies and Applications. Issue 24 (26th January 2017) - Mai, Hien Duy; Rafiq, Khezina; Yoo, Hyojong
Abstract: Nano‐ (or micro‐scale) metal‐organic frameworks (NMOFs), also known as coordination polymer particles (CPPs), have received much attention because of their structural diversities and tunable properties. Besides the direct use, NMOFs can be alternatively used as sacrificial templates/precursors for the preparation of a wide range of hybrid inorganic nanomaterials in straightforward and controllable manners. Distinct advantages of using NMOF templates are correlated to their structural and functional tailorability at molecular levels that is rarely acquired in any other conventional template/precursor. In addition, NMOF‐derived inorganic nanomaterials with distinct chemical and physical properties are inferred to dramatically expand the scope of their utilization in many fields. In this review, we aim to provide readers with a comprehensive summary of recent progress in terms of synthetic approaches for the production of diverse inorganic hybrid nanostructures from as‐synthesized NMOFs and their promising applications. Abstract : Sacrificial templates based on NMOFs are described for the preparation of a wide range of nanomaterials because of their structural and functional tailorbility at molecular levels. In the current Review, a comprehensive summary of recent progress in terms of synthetic approaches for the production of diverse inorganic hybrid nanostructures from as‐synthesized NMOFs and their promising applications is described.